Development of Virtual Reality-Based Electric Motor Control Simulation for Improving Electric Motor Installation Competency in Vocational High Schools - Ramdhan, Rizal Muhammad; Ismara, Ketut Ima; Ramelan, Agus (DPTE FT UNY, 2025)
Many vocational schools in Indonesia face limitations in laboratory facilities and practical equipment, which hinders students’ ability to master electric motor installation competencies. Virtual Reality (VR) offers a potential solution by providing safe, interactive, and cost-efficient learning environments that simulate real laboratory conditions. This study aims to develop and assess the feasibility of a VR-based electric motor control simulation as instructional media for vocational high schools. The novelty of this research lies in integrating pedagogical, ergonomic, and occupational safety aspects into VR learning, which are rarely addressed in previous studies. A Research and Development (R&D) approach was employed using a modified Waterfall model. Three-dimensional assets were created in Blender and implemented in Unreal Engine 5 to build immersive virtual environments. Validation was conducted by two media experts, two material experts, and 73 vocational students using questionnaires, observations, and pre/post-tests. The results showed feasibility scores of 68.53% from media experts and 79.58% from material experts, both categorized as feasible. Reliability analysis confirmed Cronbach’s Alpha values above 0.75, while student trials indicated significant learning improvement. These findings demonstrate that the developed VR simulation is feasible and effective as a pre-practical learning tool. In conclusion, this study contributes theoretically by extending VR pedagogy to safety-oriented vocational training and provides practical implications as an innovative solution for schools with limited resources.